Risk minimization for a portfolio using mean absolute deviation and conditional value-at-risk / Iylia Lyiana Rahim ... [et al.] - Rahim, Iylia Lyiana; Maasar, Mohd Azdi; Mohd Jamil, Siti Ayuni; Mohd Aziz, Nur Anis (UiTM Cawangan Negeri Sembilan, 2022)
Portfolio selection is one of the major problems in finance since the expected return of the assets is unknown at the time of investment is made. Usually, investors will seek to invest in assets that will yield higher returns and possess lower risks. In order to make better decision-making, investors should conduct a thorough decision analysis in selecting the stocks for their portfolio investment, as well as to determine the ways of distributing amount of money to several assets.